Development of Android Application-Based Teaching Materials for Physical Education, Health and Recreation Students - Ade Ros Riza; Eva Faridah; Deni Rahman Marpaung; Filli Azandi (AL-ISHLAH: Jurnal Pendidikan, 2023)
This development research attempts to improve learning outcomes and sports science, especially physical fitness. The programme uses learning apps and instructional videos. In each face-to-face session, the learning app includes lecture explanations, videos of learning variations, fitness programme preparation, and other blended learning instructions. When researchers realised students needed an independent learning curriculum to complete the 20 SKS Thematic KKN programme off campus, they came up with this proposal. Help students access all Thematic KKN lectures. The quantitative research method leverages Sugiono's R D method to develop and evaluate items that meet goals. After this investigation, students' cognitive abilities, programme compilation capabilities, and fitness activity variants will be assessed. Three experts—two material and one media—will validate the Android-based learning medium in advance. 40% know the needs analysis, and experts' validation percentage. The average validation value with a bad category is 29%–46%. The small group test has 63% validity, according to expert review. The validation value is 47%–64%, which is good enough for the large group test stage following repair. With an outstanding category, application-based learning media for physical fitness activities is developed effectively and efficiently. The large group test has 94% validity, and the average validation score is 83% to 100%. The small group test of 16 Medan State University students of Physical Education, Sports, and Recreation had a score of 66% with a good category, and the large group test of 32 students had a score of 88% with a very good category. Thus, researchers can improve student learning results in physical fitness activity classes utilising an Android-based software.